Factors of organizational justi influencing employees' turnover intention of smes in Zhongguancun - Wang, Na (2006)
Turnover is the termination of an individual's formal membership with an organization. Today high turnover rate becomes a big problem in many countries, especially in China. The general objective of this research is to determine the impact of organizationaJ justice factors ( compensation, career development opportunity, supervisor, work environment and work group) has any influence on employees' turnover intention and whether age, job tenure, job opportunity outside, and education level play a moderate role in the relationship between organizational justice and employees' turnover intention. The literature review provides detail description of former research on how these variables influence employees' turnover intention. The sample of this study comprises of the managers and line managers in Zhongguancun Science Park in Beijing, China. A sample of 200 managers and line managers were targeted, however, only 160 questionnaires were returned and collected for analyzing. For this study, the research used questionnaires as the main study instrument. Nine hypotheses were constructed and tested using SPSS program of multiple regression and hierarchical regression. The research discovered that organizational justice factors ( compensation, career development opportunity, and work environment) have a negative impact on employees' turnover intention and organizational justice factors (supervisor and work group) have no notable impact on employees' turnover intention. Age, job tenure, job opportunity outside and educational level do not play a moderate role in the relationship between organizational justice and employee turnover intention.